2015
DOI: 10.1038/gt.2015.69
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of adeno-associated virus neutralizing antibody activity for clinical application

Abstract: Patients with neutralizing antibodies (Nab) against adeno-associated virus (AAV) are usually excluded from treatment with AAV vectors. To develop a standard assay for detecting Nab inhibition activity, we systematically studied current AAV Nab assays in vitro and in vivo. Several factors were found that influence the Nab titers based on the in vitro assay, including: sera volume, AAV dose/cell, cell number and choice of transgenes. When the Nab titer assay was performed in vivo via intramuscular (IM) or system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…Here 25 μL of antibody or antiserum (as specified for individual experiments) was mixed with an equal volume containing recombinant AAV vectors (1,000-10,000 vg/cell) in tissue culture-treated, black, glass-bottom 96-well plates (Corning) and then incubated at room temperature for 30 min. Assay parameters were carefully controlled as outlined previously (30). A total of 5 × 10 4 HEK293 cells in 50 μL of medium was then added to each well, and the plates were incubated in 5% CO 2 at 37°C for 48 h. Cells were then lysed with 25 μL of 1× passive lysis buffer (Promega) for 30 min at room temperature.…”
Section: Identification Of Newly Evolved Aav Strainsmentioning
confidence: 99%
“…Here 25 μL of antibody or antiserum (as specified for individual experiments) was mixed with an equal volume containing recombinant AAV vectors (1,000-10,000 vg/cell) in tissue culture-treated, black, glass-bottom 96-well plates (Corning) and then incubated at room temperature for 30 min. Assay parameters were carefully controlled as outlined previously (30). A total of 5 × 10 4 HEK293 cells in 50 μL of medium was then added to each well, and the plates were incubated in 5% CO 2 at 37°C for 48 h. Cells were then lysed with 25 μL of 1× passive lysis buffer (Promega) for 30 min at room temperature.…”
Section: Identification Of Newly Evolved Aav Strainsmentioning
confidence: 99%
“…Various clinically relevant models have been established to characterize pre-existing anti-AAV humoral immunity and cross-reactivity 11, 12, 13, 14, 15, 16. Efforts have been made to develop strategies to overcome pre-existing anti-AAV Abs, including AAV capsid modification and decoys,17, 18, 19, 20 transient pharmacological immunomodulation,21, 22, 23, 24, 25 and plasmapheresis,24, 26 demonstrating potential for improving rAAV gene delivery by circumventing or reducing the pre-existing Abs in animal models and in humans.…”
Section: Introductionmentioning
confidence: 99%
“…15 Others have suggested that in vivo neutralization assays, in which Nabs are passively transferred to mice following human serum injection to the animals, are more sensitive than those neutralization assays performed in vitro and thus better suited for inclusion/exclusion criteria. 16 However, neutralizing assays (both in vivo and in vitro) rely on the ability of a reporter vector to transduce the target cells and mediate quantifiable expression levels that decrease proportionally to the amount of circulating transduction inhibitors. This poses a number of significant limitations to their standardization, as transduction efficiency is highly serotypedependent and, in general, the sensitivity of the assay decreases as the AAV dose increases, compromising the comparison of NAb titers between serotypes with distinct transduction efficiencies.…”
Section: In the Paper By Stanford Et Al 14 Recently Published In Resementioning
confidence: 99%
“…This notion, perhaps prudent in principle, has been recently challenged by Mingozzi and colleagues on the grounds that binding antibodies may in fact increase capsid internalization and transgene expression and thus NAb assays are better predictors of the outcome of gene transfer . Others have suggested that in vivo neutralization assays, in which Nabs are passively transferred to mice following human serum injection to the animals, are more sensitive than those neutralization assays performed in vitro and thus better suited for inclusion/exclusion criteria . However, neutralizing assays (both in vivo and in vitro) rely on the ability of a reporter vector to transduce the target cells and mediate quantifiable expression levels that decrease proportionally to the amount of circulating transduction inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation